Gender, Religion and the Environment: A University of the Western Cape Case Study - Conradie, Ernst M. (Journal for the study of religion, nature and culture, 2006)
This contribution explores the relationship between gender, religion and the environment in terms of the perceptions of a group of first-year students registered for a course on Environmental Awareness Techniques and Training at the University of the Western Cape in South Africa. The empirical investigation indicates that there is a surprisingly high level of environmental awareness amongst this group, possibly reflecting their different living conditions, but that they were unable to recognize connections between their environmental commitment, their religious affiliation and gender consciousness.